Prototyping sustainable mobility practices: user-generated data in the smart city. Issue 2 (1st February 2018) - Valdez, Alan-Miguel; Cook, Matthew; Langendahl, Per-Anders; Roby, Helen; Potter, Stephen
ABSTRACT: Although smart cities are now the subject of a growing literature, there is a paucity of research which considers how smart city projects develop on the ground. This paper begins to address this concern by exploring the development of a transport application, MotionMap, within the MK:Smart smart city programme. MotionMap aims to provide city-wide real-time transport information services. It is being developed through an ongoing dialogue sparked by the interaction of lead users and prototypes of a smart transport app. We draw on insights from Strategic Niche Management and social practice theories to explore how 'smart' might be integrated within and potentially transform the plurality of mobility practices that exist in cities.